Fashion law is in fashion - Barrantes Serrano, Rosmery Cristina (2023)
This article delves into the importance of fashion law as a new specialty that has a transversal character in its relationship with the rest of the legal specialties. It highlights the importance of consumer associations as institutions that are at the service of fashion consumers’ interests, using the Fashion Law Latam Association as an example. The existing challenges presented by fashion law are closely related to the legal specializations that are part of fashion law. Legal professionals who decide to specialize in fashion law have the advantage of advising a wide range of clients who are part of the supply chain for those products produced in the fashion industry.